Commuters' psychosocial profile and their involvement in child rearing at home - Roslan, Samsilah; Siaw, Yan Li; Ahmad, Noorlila (Elsevier, 2013)
The “commuter family” is recently on the rise in Malaysia. Though the impact of commuter families in maintaining the balance and harmony among family members remains debatable, studies relevant to this topic have been lacking in Malaysia. This paper aims to investigate the impact of commuter family on the commuters’ psychosocial state and their children's education. Using the qualitative approach, a total of 14 commuters were interviewed. Findings suggested that commuters with positive psychosocial characteristics had less emotional problems when handling children education as well as relationships with family members and friends. In contrast, commuters with negative psychosocial characteristics have more communication and family-related problems. In summary, the issues surrounding commuter families need to be addressed to ensure that family types do not affect over the years, the stability and harmony of the family institution in Malaysia and elsewhere.